Sikap Petani terhadap Risiko Produksi Padi dan Faktor-Faktor yang Mempengaruhinya - Adreng Purwoto (Jurnal Agro Ekonomi, 1993)
Since the achievement of the Indonesia rice self sufficiency level in 1984, the trend of the wetland rice yield in Java has been declining. In this regard, attention has to be paid to turn the yield trend up by reducing the existing gap between the potential and the actual yields at the farm level. To a large extent, the government has been attempting to improve the actual rice yield as well as the total rice production through the establishment of various policies and programs which influence factors other than risk and uncertainty stemming from rice production. This study aims to measure the farmers attitude toward risks as well as as to examine the socio-economic factors which influence this attitude. This study was conducted in the rainfed rice producing region, of Grobogan District, Central Java. It was assumed that farmers in rainfed area face higher production risk than those in irrigated area. By applying the "Observed Economic Behavior" method, this study found that most farmers are risk averters. This attitude is significantly determined by the size and the sparsity of the farmers' land. The risk aversion behavior become more evident as the land become smaller in size and as lands location become more sparsely. The small scale farmers have the tendency to adopt the safety-first principle. The land sparsity of tended to impede the application of proper management practices over the rice farms. The main implication of the finding would be to encourge farmers to perform collective activities on a larger and a more consolidated farm lands. This will enable the farmers to practice to better farm management.